22=-6u+2(u-3)

Simple and best practice solution for 22=-6u+2(u-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22=-6u+2(u-3) equation:



22=-6u+2(u-3)
We move all terms to the left:
22-(-6u+2(u-3))=0
We calculate terms in parentheses: -(-6u+2(u-3)), so:
-6u+2(u-3)
We multiply parentheses
-6u+2u-6
We add all the numbers together, and all the variables
-4u-6
Back to the equation:
-(-4u-6)
We get rid of parentheses
4u+6+22=0
We add all the numbers together, and all the variables
4u+28=0
We move all terms containing u to the left, all other terms to the right
4u=-28
u=-28/4
u=-7

See similar equations:

| 5-x(-6)=150 | | 2x-6=-3x+39 | | -7x+9=3x-1 | | 3(2f+5)=4(7-f | | 62x-1024=0 | | 1x+2x+715=700 | | 3+3x+6x+726=816 | | 62x+1/3x+725=624 | | -4*(x+3)=12 | | -4*x+3=12 | | 5x^2+20-100=0 | | 5x^2+20-100=- | | 5x+20=2x-40 | | 3x-6=8x-46 | | 4y^2-6=30 | | 3x+10=2(x+3)+3 | | -16=-7x-4(x+26) | | x+3.5=3.4 | | 133w+7=42 | | x/(x+15)=0.75 | | F(x))=-4x+1 | | 4(2+4x)=16x+7 | | 6(p-5)-3p=p+10 | | X=7x-70 | | 15x=93+57 | | A2+b2=89 | | 2y+18=y | | 2z+15=3z | | 3(9x-3)=5(2x+1) | | (7*x)+(5*Y)=2000 | | 14x-2=4x+6 | | -42=-3x+12 |

Equations solver categories